Maturation of the sensed electrogram amplitude over time in a new subcutaneous implantable loop recorder. - Krahn AD; Klein GJ; Yee R; Norris C (Pacing & Clinical Electrophysiology, 1997)
The cause of recurrent syncope may be difficult to determine if the diagnosis is not established from initial noninvasive and invasive testing. Eighteen patients with recurrent syncope and negative tilt table and electrophysiological testing underwent implantation of a left pectoral subcutaneous loop recorder. This device 'freezes' the preceding 7.5 or 15 minute rhythm strip after magnet application after spontaneous syncope. Baseline and follow-up electrograms were routinely recorded, and patients were followed until syncope recurred. Three patients had syncope within 1 month of implantation and were excluded from this report. Implantation electrogram amplitude was 250 ± 124 [mu]V and increased to 291 ± 114 [mu]V at 2-3 months, and increased further to 353 ± 167 [mu]V at 4-6 months (P < 0.001, ANOVA). Syncope recurred in 14 of the 15 patients. An arrhythmic basis for syncope was established (n = 7) or excluded (n = 7) in every patient who bad recurrent syncope. All syncopal episodes were associated with diagnostic sensed electrograms. The increase in sensed electrogram amplitude over time suggests a maturation of the device-tissue interface. These results support the long-term viability of this implantable monitoring technique.